THE ANALYSIS OF COSTUMER BONDING ON CUSTOMER LOYALTY TO IPHONE CUSTOMERS (STUDY CASE IN MILLENNIALS MANADO) - Menggelea, Andre Fresli; Lapian, Joyce S.L.H.V.; Wangkes, Shinta (Universitas Sam Ratulangi, 2020)
Abstract: In the process of globalization, it is inseparable from change, these changes also impact business competition, which requires companies to behave and act quickly, in order to face competition in a business environment that moves very dynamic and full of uncertainty. This research aims to analyze customer bonding on customer loyalty to iphone customers of millennials Manado. This research uses quantitative method. To collect the data, primary data collection was used through questionnaires. The scale of measurement that is used by researchers to determine the response of respondent’s response to each question is given by using the Likert Scale and derived with multiple linear regression model and has sample size of the research of 100 respondents of Millennials Manado that using iphone. The result of this study showed that Financial Bonds and Emotional Bonds has a significant effect to influencing iphone customers to purchase iphone leading to a customer loyalty. The costumer felt attached and willing to maintain the usage of this certain brand in order to preserve the financial reward that they keep receiving that helped them financially Keywords: Financial Bonds, Emotional Bonds, Customer Bonding, Customer Loyalty.